Murder at the Brightwell - Weaver, Ashley (Weaver, Ashley. Amory Ames mystery., 2014)
"Amory Ames is a wealthy young woman who questions her marriage to her notoriously charming playboy husband, Milo. Looking for a change, she accepts a request for help from her former fiance;, Gil Trent, not knowing that she'll soon become embroiled in a murder investigation that will test not only her friendship with Gil, but will upset the status quo with her husband. Amory accompanies Gil to the luxurious Brightwell Hotel in an attempt to circumvent the marriage of his sister, Emmeline, to Rupert Howe, a disreputable ladies' man. Amory sees in the situation a grim reflection of her own floundering marriage. There is more than her happiness at stake, however, when Rupert is murdered and Gil is arrested for the crime. Amory is determined to prove his innocence and find the real killer, despite attempted dissuasion from the disapproving police inspector on the case. Matters are further complicated by Milo's unexpected arrival, and the two form an uneasy alliance as Amory enlists his reluctant aid in clearing Gil's name. As the stakes grow higher and the line between friend and foe becomes less clear, Amory must decide where her heart lies and catch the killer before she, too, becomes a victim. Murder at the Brightwell is a delicious novel in which murder invades polite society and romance springs in unexpected places. Ashley Weaver's debut is a wonderful testament to the enduring delight of the traditional mystery"--